2020
DOI: 10.1002/er.5923
|View full text |Cite
|
Sign up to set email alerts
|

Review of the microheterogeneous thoria‐urania fuel for micro‐sized high temperature reactors

Abstract: Summary This paper presents a systematic review of the micro‐modular thorium‐fueled high temperature reactors (HTR) loaded with duplex fuel pellet design. Specifically, each unique criterion of the design is discussed separately in an attempt to understand the combined advantages of the proposed reactor. Micro modular HTRs have great potential as a source of electricity or industrial heat in the future. The use of thorium not only improves its economic performance and safety, but also prolongs its operation. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 77 publications
(134 reference statements)
0
12
0
Order By: Relevance
“…The use of duplex pellet designs increased the ratio of neutron capture in fertile material to neutron absorption in fissile material, resulting in prolonged fuel burnup and core life 29,31,32 . This was demonstrated by previous studies in which there was a 15% burnup improvement through the use of duplex pellets in PWR synergistically with axial pellet arrangement and checkboard rod configuration 7,27 . Although it has excellent potential, research into the use of ThO 2 ‐UO 2 duplex fuel design in other types of reactors aside PWRs is insubstantial.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The use of duplex pellet designs increased the ratio of neutron capture in fertile material to neutron absorption in fissile material, resulting in prolonged fuel burnup and core life 29,31,32 . This was demonstrated by previous studies in which there was a 15% burnup improvement through the use of duplex pellets in PWR synergistically with axial pellet arrangement and checkboard rod configuration 7,27 . Although it has excellent potential, research into the use of ThO 2 ‐UO 2 duplex fuel design in other types of reactors aside PWRs is insubstantial.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, during the rapid commercialization of nuclear power reactors in the 1950s to the 1970s, 232 Th was extensively studied on prototype scales in different types of reactor technologies 6,7 . It should be noted that thorium reactor designs, specifically the high‐temperature reactors (HTRs) and light water reactors (LWRs) variant, utilize thorium in the forms of either molten salt (ThF 4 or ThCl 4 ) or solid fuels (ThO 2 ) 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 According to the literature review, studies comparing the use of thorium-based fuel with various driver materials in HTGRs have often been conducted in prismatic block-type HTRs because of the flexible core that can support a wide range of fuel cycles. [35][36][37] Studies for PBR, on the other hand, have been conducted separately, and ThO 2 + UO 2 or ThO 2 + PuO 2 fuels have been widely used. 24,25,38,39 A recent comparative analysis between using HALEU (17 wt%) and ThO 2 + RGPuO 2 (RGPuO 2 content-37.6 wt%) in the PBR-HTR-10 reactor was conducted by Alzamly et al 40 Their results showed that core a fueled by ThO 2 + RGPuO 2 achieves a 24% longer fuel cycle than one fueled by HALEU (17 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages is the high conversion of fertile to fissile in the thermal spectrum, increasing the utilization of the fuel. This high conversion rate is because U‐233, which is generated from the Th‐232 transmutation chain, emits more neutrons per absorption than U‐235 8 …”
Section: Introductionmentioning
confidence: 99%